2016
DOI: 10.1039/c5sm01803j
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of cellulose nanofibrils in the presence of surfactants

Abstract: Cellulose nanofibrils (CNFs) present unique opportunities for rheology modification in complex fluids. Here we systematically consider the effect of ionic and non-ionic surfactants on the rheology of dilute CNF suspensions. Neat suspensions are transparent yield-stress fluids which display strong shear thinning and power-law dependence of modulus on concentration, G' ∼ c(2.1). Surfactant addition below a critical mass concentration cc produces an increase in the gel modulus with retention of optical clarity. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
93
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 52 publications
(6 reference statements)
16
93
0
Order By: Relevance
“…The lower G 0 of the CNF-EAA suspensions was expected, due to the reduction in CNF concentration by the addition of EAA dispersion and the excess of water. The transition from the linear viscoelastic region to the non-linear region increased with decreasing CNF concentration, the addition of EAA and the excess of water as expected (Quennouz et al 2015). The critical strain value, indicated by the drop in storage modulus, increased from 1.1% for the CNF paste to 2.3% for the CNF-EAA suspension with 0.7 wt% CNF dry content.…”
Section: Rheological Propertiesmentioning
confidence: 61%
“…The lower G 0 of the CNF-EAA suspensions was expected, due to the reduction in CNF concentration by the addition of EAA dispersion and the excess of water. The transition from the linear viscoelastic region to the non-linear region increased with decreasing CNF concentration, the addition of EAA and the excess of water as expected (Quennouz et al 2015). The critical strain value, indicated by the drop in storage modulus, increased from 1.1% for the CNF paste to 2.3% for the CNF-EAA suspension with 0.7 wt% CNF dry content.…”
Section: Rheological Propertiesmentioning
confidence: 61%
“…S3), which suggests that wall slip was insignificant. Oscillatory viscoelastic measurements showed that both HCNF and MCNF dispersions were viscoelastic above the gelation threshold (Nechyporchuk et al 2015;Quennouz et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that aqueous dispersions of slender and kinked CNFs display non-Newtonian rheological behavior characterized by shear thinning and pronounced viscoelastic behavior at concentrations above the gelation threshold (de Kort et al 2016;Jowkarderis and van de Ven 2015;Martoia et al 2016). Recent studies have investigated the effects of pulp source (Tanaka et al 2016), fibril dimension and concentration (Agoda-Tandjawa et al 2010), mechanical treatments (Pääkkö et al 2007), ionic strength (Dong et al 2013), pH (Fall et al 2013), as well as addition of amphiphilic molecules (Quennouz et al 2016) on the rheology of CNF dispersions. Additionally, CNFs can also assist in preparation of homogeneous dispersions of a variety of fillers and pigments, such as carbon nanotubes (Hamedi et al 2014), reduced graphene oxide (Duan et al 2016), TiO 2 (Schütz et al 2012), and CaCO 3 (Lourenço et al 2016) nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…But, the number of publications in the field is relatively few (Lowys et al 2001;Karppinen et al 2011;Quennouz et al 2016), and the conclusions are often not satisfactorily substantiated due to the inadequate investigation of the modes of interactions of NFC and other system components. The investigations are further complicated by the inadequate knowledge of the proper method of mixing of different components, which has been shown to have a major impact on the recorded rheological properties (Naderi et al 2015b;de Kort et al 2016).…”
Section: Rheological Studiesmentioning
confidence: 97%